Leontodon saxatilis Lam.: a range-expanding plant or a poorly recognized species in Poland? - Nobis, Agnieszka; Nobis, Marcin; Pierścińska, Agnieszka; Trojecka-Brzezińska, Anna (Biodiversity: Research and Conservation, 2011)
Until 2001, Leontodon saxatilis was known in Poland almost exclusively from the north-west part. However, numerous localities of the species in southern Poland were reported in recent publications and recorded in our field studies. Data on the distribution and habitat preferences of L. saxatilis at the new localities are presented and its origin in southern Poland is discussed.